Amino acid containing cross-linked co-polymer gels: pH, thermo and salt responsiveness. (24th February 2016) - Roy, Saswati Ghosh; Kumar, Anupam; De, Priyadarsi
Abstract: Amino acid based triple responsive (pH, thermo and salt) copolymer hydrogel system has been designed and synthesized from organogels obtained from copolymerization of tert -butoxycarbonyl (Boc)-valine methacryloyloxyethyl ester (Boc-Val-HEMA) and 2-(2-methoxyethoxy)ethyl methacrylate (MEO2 MA) in presence of diethylene glycol dimethacrylate (DEGDMA) cross-linker via reversible addition–fragmentation chain transfer (RAFT) polymerization technique. Poly(Boc-Val-HEMA) homopolymer gel has shown very high equilibrium swelling ratio ( SR e ) (∼56.4 in dichloromethane) in volatile organic solvents (VOCs) but SR e of copolymer organogels has decreased as a function of MEO2 MA content in the gel matrix. After the Boc group deprotection these organogels get converted into corresponding hydrogels and show swelling characteristic in aqueous medium. Again the SR e of copolymer hydrogels decreases as mole fraction of MEO2 MA increases in the gel matrices due to the decrease in interstitial porosity, as authenticated by field emission scanning electron microscopy (FE-SEM). Furthermore, all these hydrogels exhibit excellent tuneable pH, thermo and salt responsiveness which depend upon the composition of the polymer gels. Thermo-responsive property of polyelectrolyte hydrogels is pH dependent and is suppressed at low pH (pH 4) but volume phase transition of polyeletrolyte hydrogels has been observed at pH 7. Copolymer hydrogels showed higher mechanical strength compared to amino acid based superabsorbent polymer hydrogel, confirmed by rheological measurements. Graphical abstract: Highlights: Cross-linked homopolymer and copolymer gels have been synthesized. Hydrogels showed tuneable pH, thermo and salt responsive properties. The mechanical properties of copolymer hydrogels have been studied by rheology. These triple responsive gels are potential candidates for biomedical applications.